The Automation of Water Control in the Field Football With Arduino uno - Ardiansyah, Fikri Iqbaal; Nuryanto, Nuryanto; Widiyanto, Andi (Innovation, Technology, and Entrepreneurship Journal, 2024)
Football is not only carried out as an ordinary sport, but the sporting achievement itself is an asset that can popularize a region or country. In the smooth running of sports activities, stadium facilities were established to support the success of playing soccer. During the rainy season, the match will be disrupted due to the fact that the football field has excessive water, which hinders the match. The system used today to control excessive water on the soccer field is by using an impregnation system. Therefore, a tool is needed that can help reduce excess water during heavy rains. So a prototype water control device was designed on a football field using a soil moisture sensor that can detect soil moisture, using a water pump assisted by a relay to reduce the presence of excess water, as well as using a servo to raise and lower the tools used to spray water and also suck up water. All of these design components are controlled by Arduino uno. This test process if the soil is in soil moisture < 45% then Arduino orders the tool to work because at that humidity the soil is dry. If the soil moisture is > 55%, the servo and also the relay are ordered to work because at that humidity the soil is wet